2018
DOI: 10.1128/jb.00218-18
|View full text |Cite
|
Sign up to set email alerts
|

Updates to Clostridium difficile Spore Germination

Abstract: Germination of spores is a crucial early requirement for colonization of the gastrointestinal tract. Likewise, cannot cause disease pathologies unless its spores germinate into metabolically active, toxin-producing cells. Recent advances in our understanding of spore germination mechanisms indicate that this process is both complex and unique. This review defines unique aspects of the germination pathways of and compares them to those of two other well-studied organisms, and germination is unique, as does not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 100 publications
1
57
1
2
Order By: Relevance
“…However, since heavy metals were only at trace concentrations in BG-11 and Cyanothece sp. PCC 7425, and G. lithophora C7 are not filamentous, none of these functions apply to explain the differences in Ca requirements between cyanobacterial strains forming intracellular ACC.Similarly, high amounts of Ca are needed by sporulating bacteria(Stewart et al, 1980) for resistance of spores to wet heat (e.g.,Kochan et al, 2018). Again, there is no obvious connection with the cyanobacteria studied here, since they do not sporulate.…”
mentioning
confidence: 68%
“…However, since heavy metals were only at trace concentrations in BG-11 and Cyanothece sp. PCC 7425, and G. lithophora C7 are not filamentous, none of these functions apply to explain the differences in Ca requirements between cyanobacterial strains forming intracellular ACC.Similarly, high amounts of Ca are needed by sporulating bacteria(Stewart et al, 1980) for resistance of spores to wet heat (e.g.,Kochan et al, 2018). Again, there is no obvious connection with the cyanobacteria studied here, since they do not sporulate.…”
mentioning
confidence: 68%
“…(B) Purification of CspC-His 6 variants from the soluble fraction. G171R was included because this mutation had been predicted to destabilize CspC by steric occlusion [21, 32]. Cultures expressing the cspC variants were induced with IPTG overnight at 18°C, and aliquots were removed for analysis of the “induced” fraction.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, C. difficile infections begin when its metabolically dormant spores germinate in the gut of vertebrate hosts in response to bile acids [20]. Notably, unlike almost all other spore-formers studied to date, C. difficile senses bile acid germinants instead of nutrient germinants [21, 22]. The bile acid germinant signal is transduced by clostridial serine proteases known as the Csps [23-26], which are members of the subtilisin-like serine protease family members [27, 28] conserved in many clostridial species [29].…”
Section: Introductionmentioning
confidence: 99%
“…Further analyses revealed that some of these mutations alter sensitivity to amino acid and/or calcium co-germinants, which potentiate bile salt-induced germination in C. difficile . Since the mechanism by which co-germinants are sensed by C. difficile spores was previously unknown [19, 20], our study reveals for the first time that C. difficile CspC integrates multiple germinant and co-germinant signals to induce spore germination and raises important new questions regarding how these signals are specifically sensed and transduced.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, recent studies indicate that C. difficile ’s germination pathway is unique among other spore forming organisms [19, 20]. Almost all spore-forming organisms studied to date encode transmembrane germinant receptors of the Ger family [21, 22], which sense nutrient germinants, like amino acids, nucleic acids, and sugars [23].…”
Section: Introductionmentioning
confidence: 99%